2009
DOI: 10.1002/hlca.200900041
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Rearrangements of Monoterpenes and Monoterpenoids

Abstract: On the occasion of the 70th anniversary of the Nobel Prize in Chemistry awarded to Leopold Ružička for his work on polymethylenes and higher terpenes 1 )The thermal conversions of monoterpenes and monoterpenoids are an interesting field of research with respect to mechanistic, kinetic, and theoretical issues. Since the beginning of the 20th century, these reactions have attracted the interest of many research groups, and even today there are sufficient problems and questions to deal with. This review covers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
52
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 154 publications
8
52
0
Order By: Relevance
“…Kinetic models were constructed for the rearrangement of cisand trans-2-pinanol which are able to predict the reactant reactivities, product yields and selectivities. Both kinetic models are based on the mechanism for thermal rearrangement of bicyclic monoterpenes containing a [3.1.1]bicycloheptane system that has been reported in literature [26,39]. A stepwise fragmentation of the cyclobutane ring with biradical intermediates is generally accepted as the initial decomposition of the reactant molecules.…”
Section: Cis-2-pinanolmentioning
confidence: 99%
See 2 more Smart Citations
“…Kinetic models were constructed for the rearrangement of cisand trans-2-pinanol which are able to predict the reactant reactivities, product yields and selectivities. Both kinetic models are based on the mechanism for thermal rearrangement of bicyclic monoterpenes containing a [3.1.1]bicycloheptane system that has been reported in literature [26,39]. A stepwise fragmentation of the cyclobutane ring with biradical intermediates is generally accepted as the initial decomposition of the reactant molecules.…”
Section: Cis-2-pinanolmentioning
confidence: 99%
“…Stolle et al investigated the mechanism and kinetics of the gasphase isomerization of monoterpenes [26,31] and showed that there are mechanistic analogies in the isomerization of pinaneand pinene-type structures. Moreover, the authors were able to model reactivity differences between cis-pinane and trans-pinane.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Two recent reviews [7,8] have described only the thermal transformations of some monoterpenes and monoterpenoids in SCFs; whereas the other types of reactions remain undiscussed. This review covers all types of transformations of monoterpenes and monoterpenoids in SCFs, which have been published up to early 2012, including the results obtained by the authors and literature data.…”
mentioning
confidence: 97%
“…Since the formation of compounds with cyclopentane skeleton 7 and 8 by thermal isomerization seems unlikely, 11 even residual acidity of supercritical media in the presence of triethylamine appears sufficient for initiation of verbenol epoxide 5 transformations. In the presence of ZnBr 2 verbenol epoxide 5 transforms into compound 7, 12 while in the presence of Montmorillonite clay the main product is compound 6 (44% yield); compounds with cyclopentane skeleton 7 and 8 are formed in smaller quantities (16 and 10%, respectively).…”
mentioning
confidence: 99%